Childhood cancer in general practice: Is it really that rare?. Issue 4 (April 2017) - Kelly, Jennifer
Childhood cancer is something most GPs think to be rare, yet it is the biggest medical cause of death in children aged between 1 and 14 years. Its incidence is increasing, with just under 4000 children and young people diagnosed with cancer every year in the UK (11 a day). It is important for GPs to know the signs and symptoms suggestive of childhood cancers, in order to help early diagnosis. This, in turn, can save lives and reduce disability in survivors. The number of children surviving cancer is increasing, with over 35 000 survivors now thought to be living in the UK and in need of particular expertise and care. This article aims to provide GPs with the tools and knowledge to diagnose childhood cancer, and a framework to support children with cancer and their families long-term in the community.